2008
DOI: 10.2495/st080091
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean standard for sustainable tourism (MESST) – general requirements, objectives and the philosophy of MESST

Abstract: Tourism is an activity that can have a truly major impact on sustainable development. EU recorded in excess of 440m visitor arrivals in 2005. Tourism, directly and indirectly, accounts for around 10% of European GDP and 20m jobs. Europeans account for over half of all international travel, and visits by Europeans provide an important source of income for many developing countries. In 2005 the World Tourism Organization (UNWTO) and the United Nations Environment Programme (UNEP) identified an agenda of 12 aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…On the other hand, although the vast majority of the informants acknowledged the importance of sustainability for the tourism development of Rhodes, several bars and restaurant owners, travel agents and yacht company managers asserted that their main concern was to maximize their profits. This finding coincides with the results of the evaluation report on MESST in 2007, in which local entrepreneurs appeared to link tourism sustainability with the potential economic viability of their businesses (Zorpas et al., 2008). Based on that report the local tourism industry believed that the main priority of sustainability was to ensure long-term economic benefits, while ensuring the optimal use of environmental resources.…”
Section: Main Textsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, although the vast majority of the informants acknowledged the importance of sustainability for the tourism development of Rhodes, several bars and restaurant owners, travel agents and yacht company managers asserted that their main concern was to maximize their profits. This finding coincides with the results of the evaluation report on MESST in 2007, in which local entrepreneurs appeared to link tourism sustainability with the potential economic viability of their businesses (Zorpas et al., 2008). Based on that report the local tourism industry believed that the main priority of sustainability was to ensure long-term economic benefits, while ensuring the optimal use of environmental resources.…”
Section: Main Textsupporting
confidence: 89%
“…The Mediterranean Standard for Sustainable Tourism ( MESST) aimed to generate the transnational collaboration among Mediterranean countries, increase the competitiveness of tourism enterprises, upgrade the quality of tourism products/services and create an international zone of economic integration based on Barcelona principles (Zorpas et al., 2008). The overall objective of MESST was to develop a recognizable, applicable, voluntary, sustainability standard for Mediterranean destinations and tourism businesses.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…OSH is frequently pointed as a challenge for SMEs. Several factors have been identified to explain differences in OSH performance between SMEs and large enterprises, in particular the following ones: limited financial, human and technological resources; reduced knowledge about OSH matters by the employers; limited time to deal with these matters by the employer; attitudes of employers and workers away from OSH issues; difficulties in fulfil with legal requirements (Barbosa et al, 2019;Bonafede et al, 2016;Cagno et al, 2011;Champoux & Brun, 2003;Hasle et al, 2012;Mayhew, 2000;Micheli & Cagno, 2008;Masi & Cagno, 2015;Reinhold et al, 2015;Zorpas et al, 2008).…”
Section: Osh As a Challenge For Smesmentioning
confidence: 99%
“…Additionally, it was suggested that the responses of VSME to new requirements of the market were restricted through little access to further training; non participate in knowledge transfer or developing cross firm federation whilst producing high levels of waste (Zorpas et al, 2008). However, contradictory research suggests that SME"s experience distinct advantages over non-SME"s when implementing green initiatives including less bureaucracy, quicker response time and efficient internal communication (Van Hemel and Cramer, 2002).…”
Section: Classification Through Organisational Sizementioning
confidence: 99%